Telaah Fiqh Muamalah Dan Nilai Akuntansi Dalam Tradisi Sanamang Dan Dudu Tampa Di Desa Tulehu, Kota Ambon - Zakaria, Ilham Habibi; Zakaria, Syawal (DIALEKTIKA, 2024)
Culture is one of the identities that each region possesses with its own character. The traditions of sanamang and dudu tapas are one of them. The tradition is a series of weddings in Tulehu village, Ambon town, Maluku. This research aims to examine the cultural reality of sanamang and dudu tampa through expression fiqh muamalah and accounting values. The method used is qualitative with data aggregation with interview techniques and literary studies. Based on the results of the study that the traditions of sanamang and dudu tampa carry a holistic value. These values are manifested in the attitude of ta'awun (help-help) as part of the value of muamalah which is definitely allowed to be the main value of the tradition of sanamang and dudu tampa practices. Another important aspect is the value of transparency and accountability expressed through the implementation of sanamang and dudu tampa. This increasingly gives the belief that culture, spirituality, and accounting are directly connected into an inseparable unity.